An anthropologist’s voice in a veterinarian’s noise: gearing up for new cultural realities - Šterk, Karmen; Brložnik, Maja (Frontiers in Veterinary Science, 2023)
Over the past three decades, the veterinary profession has faced a cultural shift towards postspeciesism that requires a reassessment of the foundations of the existing distinctions between human and non-human animals proclaimed by the speciesism paradigm, which represents institutionalized discrimination against species and recognizes only the subjectivity of humans. Based on ethnographic observations in anthropological fieldwork and using speciesism/postspeciesism distinction, we aimed to explain the main causes of small animal practitioners’ work-related stress and apply humanistic knowledge to recommend ways to alleviate the negative effects of the work environment. The explanatory model of disease, illness, and sickness, the example of the concept of family, and the circumstances of the feminization of the veterinary profession are discussed to illustrate the divergence between speciesist naturalistic veterinary knowledge and the postspeciesist cultural framework and its consequences. By failing to accommodate the changing values towards animals and by failing to challenge the anthropocentric hierarchy of values, the speciesist rationale of the veterinary profession contributes to many of the problems faced by practicing veterinarians. The incorporation of a modern moral-philosophical mindset towards animals may not even be possible because veterinary science is subject to a paradigm that is irreversibly tied to institutional discrimination against species and defies reflection on veterinary science itself. However, the veterinary profession has a privileged position in establishing an alternative ontological thinking and an alternative conception of “animal life”. Anthropological knowledge was applied to anticipate further intervention of social and cultural sciences in the problems of small animal practitioners. Rather than further diversifying and increasing expectations towards veterinarians by expecting them to acquire additional skills, we propose another practitioner who can support, mediate, and enhance veterinary performance – the cultural anthropologist. With their deep knowledge of cultural differences and social dynamics, they can collaborate with veterinarians to act as a liaison between cultures, paradigms, and species.